Clinical heterogeneity of neuro-inflammatory PET profiles in early Alzheimer’s disease - Gouilly, Dominique; Salabert, Anne-Sophie; Bertrand, Elsa; Goubeaud, Marie; Catala, Hélène; Germain, Johanne; Ainaoui, Nadéra; Rafiq, Marie; Benaiteau, Marie; Carlier, Jasmine; Nogueira, Leonor; Planton, Mélanie; et al. (Frontiers in Neurology, 2023)
The relationship between neuroinflammation and cognition remains uncertain in early Alzheimer’s disease (AD). We performed a cross-sectional study to assess how neuroinflammation is related to cognition using TSPO PET imaging and a multi-domain neuropsychological assessment. A standard uptake value ratio (SUVR) analysis was performed to measure [18F]-DPA-714 binding using the cerebellar cortex or the whole brain as a (pseudo)reference region. Among 29 patients with early AD, the pattern of neuroinflammation was heterogeneous and exhibited no correlation with cognition at voxel-wise, regional or whole-brain level. The distribution of the SUVR values was independent of sex, APOE phenotype, early and late onset of symptoms and the presence of cerebral amyloid angiopathy. However, we were able to demonstrate a complex dissociation as some patients with similar PET pattern had opposed neuropsychological profiles while other patients with opposite PET profiles had similar neuropsychological presentation. Further studies are needed to explore how this heterogeneity impacts disease progression.